Depiction of Chamunda in the bhadra - Temples of India Project Team (Jio Institute, 2024)
The jangha on the south wall of the garbhagriha depicts Chamunda in the bhadra. The six-armed Goddess is shown standing on a human body. She is holding a knife, trishula (trident), and damaru (hourglass-shaped drum) in her right hand. In her left hand, she is holding a bowl and a khatwang (staff with a skull at the top) and in her middle hand, she is touching her lip. She is shown with an emaciated body, dried and saggy breasts and a sunken belly. She has a jatamukuta and is adorned with ornaments. It is worth noticing that she is wearing a snake as her waist belt.